Comparative characterization of the gluten and fructan contents of breads from industrial and artisan bakeries: a study of food products in the Spanish market - Marín Sanz , Miriam; Sánchez-León , Susana; León , Elena; Barro , Francisco (Food & Nutrition Research, 2022)
Background: The consumption of wheat/gluten is associated with adverse reactions for human health. Gluten and fructans are identified as the major compounds triggering and worsening adverse reactions to wheat, which are increasing, and as a consequence, avoidance of gluten/wheat is the common strategy of many individuals of the western population. Although bread is a product of daily consumption, there is a lack of information on the gluten and fructan contents and the influence of artisanal or industrial processes.Objective: The aim of this study is to carry out a comparative characterization between artisan bakeries and hypermarkets in Spain for gluten and fructan contents in daily sold breads.Design: A total of 48 types of bread highly consumed in Spain sold in artisan bakeries (long fermentation) and hypermarkets (short fermentations) were selected for comparing the gluten and fructan contents. Methods such as reverse phase-high performance liquid chromatography (RP-HPLC), R5 monoclonal antibody (moAb), and fructans protocols were used for the quantification of these compounds.Results: Great variation for the content of gluten and fructans has been found between all bread categories. Although breads produced using long fermentation (artisan bakeries) contain significantly lower gluten, they have higher fructans than those using short fermentations (hypermarkets). Durum wheat breads had the lowest content of gluten. Moreover, spelt breads from artisan bakeries had the lowest content of fructans but not those from hypermarkets.Discussion: In this study, we report the comparative characterizarion of the breads of the Spanish market. These food products presented variation in the amount of gluten and fructans, ligated in most of the cases to the nature of the providers: artisan bakeries against hypermarkets. Depending on the type of bread, the differences for the daily consumption of gluten and fructan can be 4.5 and 20 times, respectively.Conclusions: We found strong differences for gluten and fructan contents among breads. These information may contribute to designing strategies to improve the management of gluten and fructans in bread.